In‐hospital and 1 year incremental prognostic value of drug abuse detection in acute heart failure - Charles Fauvel; Jean‐Guillaume Dillinger; Thomas Bochaton; Thomas Levasseur; Amine El Ouahidi; Cyril Zakine; Antony El Hadad; Nicolas Mansencal; Nathalie Noirclerc; Marc Goralski; Christophe Thuaire; Nathan Mewton; et al. (ESC Heart Failure, 2025)
Abstract Aims The study aims to assess the in‐hospital and 1 year incremental prognostic value of recent drug abuse use, detected by a systematic urinary screening, in a consecutive cohort of patients hospitalized for acute heart failure (AHF). Methods All patients admitted for AHF with a drug abuse screening using a urinary assay were included in this prospective multicentric study (39 French centres). The outcomes were (i) in‐hospital major adverse cardiovascular events (MACEs) defined as all‐cause death, resuscitated cardiac arrest or cardiogenic shock; and (ii) 1 year MACEs defined as cardiovascular death or hospitalization for AHF. Incremental prognostic value was assessed using the C‐index, the global χ2 and likelihood‐ratio (LR) test, the net reclassification improvement (NRI) and integrated discrimination improvement (IDI). Results In total, 458 patients with AHF were included (mean age 68 ± 14 years, 67% male, 79% of new heart failure onset). In‐hospital and 1 year MACEs occurred, respectively, in 65 (14.2%) and 129 (28.2%) patients. Drug abuse detection was independently associated with in‐hospital MACEs [model 1—known comorbidities: odds ratio (OR) = 4.46, 95% confidence interval (CI) (1.88–10.3), P < 0.001; model 2—clinical severity: OR = 3.64, 95% CI (1.56–8.26), P = 0.002], even after propensity‐matched population analysis [OR = 3.34, 95% CI (1.32–8.70), P = 0.011], with a significant incremental prognostic value over and above traditional risk factors (C‐statistic improvement 0.04 with LR test P < 0.001 for both models). Patients with drug abuse detection had worse 1 year survival: HR = 1.82, 95% CI (1.13–2.92), P = 0.012. Drug abuse detection was independently associated with 1 year MACEs after adjustment with traditional prognosticators [OR = 2.54, 95% CI (1.28–4.98), P = 0.008] and propensity‐matched population analysis [OR = 2.77, 95% CI (1.98–5.21), P = 0.001], with an incremental prognostic value as well (C‐statistic improvement 0.02, LR test P < 0.001, positive NRI and IDI). Conclusions Drug abuse use was independently associated with a higher occurrence of both in‐hospital and 1 year MACEs with an incremental prognostic value. These results suggest a potential interest of a systematic illicit drug screening in these patients. TRIAL REGISTRATION ClinicalTrials.gov Identifier: NCT05063097.